Quantitative Estimation of Abrasion Loss from Strength of Sandstone Rocks of Salt Range, Pakistan - Arslan, M.; Yaqub, M.; Khan, M. S. (The Nucleus, 2015)
Evaluation of degradation or abrasion loss through Los Angeles abrasion loss is tedious and time consuming due preparation of samples of different grading. Hence there is a need to explore relations through other indirect methods which are simple, fast and more economical such as Schmidt rebound hammer test and Point load strength index test. In this research work, an attempt is made to develop a quantitative relationship for the estimation of Los Angeles abrasion loss through Schmidt hammer hardness and Point load strength. The results of Schmidt rebound hammer test and Point load strength index test, carried out on thirty one Sandstone samples collected from various location of Salt Range Pakistan, were correlated with corresponding values of Los Angeles abrasion test. To evaluate the correlation equations and coefficients of correlations, the data of these tests was statistically analyzed through linear regression analysis. A strong inverse relationship exists between Los Angeles abrasion loss and Point load strength while the inverse relationship between abrasion loss and Schmidt hammer hardness is relatively weaker. Â©